PERAN PEMERINTAH DALAM PEMBERDAYAAN PETANI TANAMAN PORANG DI KABUPATEN SINJAI - Miftahul Haerat; Muhammad Isa Ansari; Fatmawati Fatmawati (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to find out the role of the government in empowering porang farmers in Sinjai Regency. This study used a qualitative research method with a descriptive type of research. Data collection techniques were observation, interviews and documentation. The informants in this study consisted of 7 (seven) people who were determined by purposive sampling. The results of this study showed 4 (four) indicators of the role of the government of the Department of Horticulture and Plantation in Sinjai Regency, namely: 1) As a facilitator, the presence of the government in empowering porang farmers was very important because it could provide information to farmers about porang plants and the government also facilitating farmers 2) As an innovator, the government provided innovation to farmers about porang cultivation techniques and the government cooperated with banks and CV companies. Celebes 3) As a Modernizer, the Government led farmers towards modern life, namely the ability to master science and technology as well as the ability to process natural wealth 4) As a Pioneer, the Government became a role model for farmers, for example managing materials that used to only pollute the environment and could be processed and utilized by farmer.